Research on the Differences in The Average Daily Gain Recorded in Aubrac Bulls - Bianca-Maria Mădescu; Roxana Lazăr; Andra-Sabina Neculai-Văleanu; Ioana Poroșnicu; Paul Corneliu Boișteanu (Scientific Papers Animal Science and Biotechnologies, 2023)
The purpose of this paper is to highlight the difference in the average daily gain recorded in the bulls of the Aubrac breed, exploited in the conditions of our country. The database was made up of data recorded in two fattening bull farms of the Aubrac breed. The average daily gain of the animals recorded at the age of 12 months, as well as the average daily gain at the age of 18 months, were measured. A total of 30 animals (15 animals from farm 1, and 15 animals from farm 2) were studied. The results were statistically interpreted, which showed that there were no significant differences between the animals from the two studied farms, but there were statistically significant differences between the average daily increase recorded at 12 months compared to the average daily increase recorded at 18 months.